Research Progress on the Formation Pathway and Regulation of Trans Fatty Acids in Vegetable Oils - LIANG Manzhu, HU Yumeng, LI Zhenyuan, HUANG Xuegang, BELLO Zaki Abubakar, GUO Qin, WANG Qiang (Shipin Kexue)
Trans fatty acids (TFAs) have attracted considerable attention from all sectors of the community. As vegetable oils are the major source of TFAs in the daily diet, it is essential to understand the formation of TFAs in vegetable oils for accurate regulation. In recent years, a number of studies have explored the amount of TFAs generated in different vegetable oils and breakthroughs have been made in understanding the formation pathways and regulatory mechanisms of different TFAs isomers, but a systematic and comprehensive review has not yet been conducted. In this review, a systematic summary of the types and contents of TFAs in different vegetable oils, their formation mechanisms, regulatory measures and mechanisms is presented, with a view to providing references for people’s daily intake of TFAs through vegetable oils as well as subsequent research on TFAs in vegetable oils.